Adsorption of Chromium Ions on Activated Carbon Produced from Cow Bones - Waleed Khalid, Marah; D. Salman, Sami (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
Due to the broad range uses of chromium for industrial purposes, besides its carcinogenic effect, an efficient, cost effective removal method should be obtained. In this study, cow bones as a cheap raw material were utilized to produce active carbon (CBAC) by physiochemical activation, which was characterized using: SEM to investigate surface morphology and BET to estimate the specific surface area. The best surface area of CBAC was 595.9 m2/gm which was prepared at 600 ᵒC activation temperature and impregnation ratio of 1:1.5. CBAC was used in aqueous chromium ions adsorption. The investigated factors and their ranges are: initial concentration (10-50 mg/L), adsorption time (30-300 min), temperature (20-50 ᵒC) and solution pH (2-11). Isotherm of adsorption and its kinetics were studied. The adsorption process was modeled statistically and was represented by an empirical model. Equilibrium data were fitted to the Langmuir and Freundlich isotherm models and the data best represented by Freundlich isotherm. Pseudo- first order and pseudo- second order kinetic equations were utilized to study adsorption kinetics, where chromium adsorption on CBAC fitted pseudo- second order fitted the data more adequately. The best removal efficiency was found to be 94.32%.